Gingival Enlargement as a Manifestation of Osseous Choristoma: Case Report and Management - Rosa, Roberta Rezende; Paulo, Luiz Fernando Barbosa de; Oliveira Júnior, Anísio Domingos de; Durighetto Junior, Antonio Francisco (Journal of Oral Diagnosis, 2016)
The term choristoma describes a hamartomatous tumor-like lesion composed of normal tissue in an abnormal location and are designated according to the tissues from which they are derived. Typically, osseous choristomas of the oral cavity present as slow growing masses in the tongue, and rare cases are reported in the buccal mucosa and in the alveolar ridge. To our knowledge, few cases of gingival osseous choristoma have been reported, and the clinical differential diagnoses are very important for the practitioners. This report presents a rare location of a choristoma which by the clinical appearance and microscopic findings was shown to be an osseous choristoma presented in alveolar mucosa.